2013
DOI: 10.1186/1471-2164-14-431
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic analysis of six bacteria belonging to the genus Novosphingobium: insights into marine adaptation, cell-cell signaling and bioremediation

Abstract: Background: Bacteria belonging to the genus Novosphingobium are known to be metabolically versatile and occupy different ecological niches. In the absence of genomic data and/or analysis, knowledge of the bacteria that belong to this genus is currently limited to biochemical characteristics. In this study, we analyzed the whole genome sequencing data of six bacteria in the Novosphingobium genus and provide evidence to show the presence of genes that are associated with salt tolerance, cell-cell signaling and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 57 publications
5
45
0
1
Order By: Relevance
“…This phylogenomic tree showed that three strains isolated from the copper mine (namely, ZJ, DX, and ZBY) were clustered together (group 2 in Figure 2 ). Similarly, an earlier study reported that taxonomic clustering of six strains belonging to the genus Novosphingobium was generally influenced by their respective source of isolation (Gan et al, 2013). Further inspection revealed that the geographic distribution of strain ZBY was distinctively differed from those of the other two strains (ZJ and DX), and the genome-content-based distance matrix implied a slight evolutionary divergence ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 78%
“…This phylogenomic tree showed that three strains isolated from the copper mine (namely, ZJ, DX, and ZBY) were clustered together (group 2 in Figure 2 ). Similarly, an earlier study reported that taxonomic clustering of six strains belonging to the genus Novosphingobium was generally influenced by their respective source of isolation (Gan et al, 2013). Further inspection revealed that the geographic distribution of strain ZBY was distinctively differed from those of the other two strains (ZJ and DX), and the genome-content-based distance matrix implied a slight evolutionary divergence ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 78%
“…This broad range of genome sizes is reflected in the diversity of gene repertoires: only a tiny minority of prokaryotic genes are (nearly) universal whereas the great majority are present in small subsets of genomes [6,10,11]. Substantial differences in genome size and gene content are often evident between species within the same genus [12][13][14] and even between strains of the same species [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Statistical significance from analysis of variance of fertilizer amendments, cultivar and fertilizer amendments · cultivar interaction for soil pH, organic carbon, and enzyme activities. recently, this group has been discovered in plant-associated habitats such as the internal stem of Gossypium hirsutum (K€ ampfer et al, 2015), the rhizosphere of Arabidopsis thaliana (Gan et al, 2013), and surface of a crown gall tumor on grapevine (Lin et al, 2014). One suggestion for Novosphingobium association with plants in the rhizosphere is the presence of xenobiotic aromatic compounds.…”
Section: Resultsmentioning
confidence: 99%